Crystal engineering of a rectangular sql coordination network to enable xylenes selectivity over ethylbenzene. Issue 26 (23rd June 2020) - Kumar, Naveen; Wang, Shi-Qiang; Mukherjee, Soumya; Bezrukov, Andrey A.; Patyk-Kaźmierczak, Ewa; O'Nolan, Daniel; Kumar, Amrit; Yu, Mei-Hui; Chang, Ze; Bu, Xian-He; Zaworotko, Michael J.
Abstract : [Co(bipy)(bptz)(NCS)2 ] n, a new mixed-linker sql coordination network, exhibits high xylene adsorption capacity and high xylene selectivity over ethylbenzene (>5). Abstract : Separation of the C8 aromatic isomers, p -xylene (PX), m -xylene (MX), o -xylene (OX) and ethylbenzene (EB), is relevant thanks to their widespread application as chemical feedstocks but challenging because of their similar boiling points and close molecular dimensions. Physisorptive separation could offer an energy-efficient solution to this challenge but sorbents which exhibit strong selectivity for one of the isomers remain a largely unmet challenge despite recent reports of OX or PX selective sorbents with high uptake capacity. For example, the square lattice, sql, topology coordination network [Co(bipy)2 (NCS)2 ] n (sql-1-Co-NCS) exhibits the rare combination of high OX selectivity and high uptake capacity. Herein we report that a crystal engineering approach enabled isolation of the mixed-linker sql coordination network [Co(bipy)(bptz)(NCS)2 ] n (sql-1, 3-Co-NCS, bipy = 4, 4′-bipyridine, bptz = 4, 4′-bis(4-pyridyl)tetrazine) and study of its C8 vapour and liquid sorption properties. sql-1, 3-Co-NCS was found to exhibit high adsorption capacity from liquid xylenes (∼37 wt%) and is to our knowledge the first sorbent to exhibit high selectivity for each of xylene isomer over EB ( S OX/EB, S MX/EB, S PX/EB > 5). Insights into the performance of sql-1, 3-Co-NCS are gained from structural studies which reveal stacking interactions between electron-deficient bptz linkers and the respective xylenes. sql-1, 3-Co-NCS is the first N-donor mixed-linker sql coordination network studied for its gas/vapour sorption properties and represents a large and diverse class of understudied coordination networks.